Advance in Operator Theory and Jiang's Seven Questions (Communications in Mathematical Research, 2023)
In this paper we review the seven questions posed by Professor JiangZejian and summarize the progress of them. Moreover, we introduce those applications of tools developed in studying Jiang's questions, especially in dealing with the Halmos' third problem.
Keywords: BIR operator; geometric operator; Halmos’ third question.